2023
DOI: 10.1021/acsmaterialslett.3c00320
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healing Hydrogels: From Synthesis to Multiple Applications

Abstract: Due to the good reliability and long-term stability, self-healing hydrogels have emerged as promising soft materials for tissue engineering, smart wearable sensors, bioelectronics, and energy storage devices. The self-healing mechanism depends on reversible chemical or physical cross-linking interactions. Self-healing hydrogels with fascinating features (including mechanical performances, biocompatibility, conductivity, antibacterial ability, responsiveness, etc.) are being designed and developed according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(21 citation statements)
references
References 268 publications
0
13
0
Order By: Relevance
“…75 However, most physical crosslinking techniques are dependent on the inherent properties of the polymer matrix, limiting the ability to modify hydrogel properties on demand. 76 By forming covalent bonds between polymer chains, chemical crosslinking accomplishes gelation, resulting in the formation of hydrogels with enhanced stability and persistence. 77 In addition, chemical crosslinking allows the incorporation of specific functional groups or chemical modification using various crosslinkers and reaction conditions to impart particular properties and functions to hydrogels.…”
Section: Nanocellulose and Nanocellulose Hydrogelsmentioning
confidence: 99%
“…75 However, most physical crosslinking techniques are dependent on the inherent properties of the polymer matrix, limiting the ability to modify hydrogel properties on demand. 76 By forming covalent bonds between polymer chains, chemical crosslinking accomplishes gelation, resulting in the formation of hydrogels with enhanced stability and persistence. 77 In addition, chemical crosslinking allows the incorporation of specific functional groups or chemical modification using various crosslinkers and reaction conditions to impart particular properties and functions to hydrogels.…”
Section: Nanocellulose and Nanocellulose Hydrogelsmentioning
confidence: 99%
“…Additionally, research has demonstrated that UDC speeds up wound healing and promotes tissue regeneration in addition to its anti-inflammatory properties. , For the sustained release of drug at the targeted sites, it can be incorporated in some stimuli-responsive polymer-based materials. It is to be noted that the drug delivery through natural polymer-based adhesive and stimuli-responsive self-healing hydrogels provides some extra benefits such as better adhesion with the skin as well as wound, biocompatibility, adaptability, resemblance with the natural tissues, tunability, and biodegradability …”
Section: Introductionmentioning
confidence: 99%
“…Flexible wearable strain sensors have attracted extensive attention because of their substantial applications in health management, electronic skins, human–machine interfaces, soft robotics, and more. Conductive hydrogels have brought many opportunities for flexible strain sensors due to their good conductivity, self-healing ability, stretchability, tunable conducting channels, biocompatibility, compliance, and affinity with the skin. However, many existing hydrogels still suffer from some drawbacks and cannot meet the needs of long-term and stability sensing applications. First, many existing conventional conductive hydrogels using water as the dispersion medium inevitably freeze at subzero temperatures, dehydrate in the air at a relatively high temperature, and thus become rigid, fragile, and non-conductive .…”
Section: Introductionmentioning
confidence: 99%